Analisis Spasial Kejadian Malaria Ditinjau dari Kepadatan Penduduk, Akses Sanitasi Layak, dan Ketersediaan Fasilitas Kesehatan di Kabupaten Kota Provinsi Sumatera Utara - Yolanda D.B Manullang; Nenis Gusnawati Laia; Windha Khaila Shabrina; Sindy Nafsya Aprilia; Vierto Irennius Girsang (SEHATI: Jurnal Kesehatan, 2025)
Malaria is an infectious disease caused by parasites and transmitted through the bite of Anopheles mosquitoes. This disease is acute, potentially fatal, and becomes one of the serious public health issues worldwide. WHO data in 2023 estimates there are 263 million cases of malaria with approximately 597,000 deaths. In 2024, there were 418,546 cases in Indonesia. Data from the Central Statistics Agency of North Sumatra Province shows that in North Sumatra, 6,696 malaria patients were found in 2024. The aim of this study is to identify the risk factors for the occurrence of malaria. The research method used is a literature review by searching and mapping existing literature. The study was conducted using various sources including books, journals, articles, and other sources that can be used in the literature review process. Based on the research, the risk of contracting malaria is caused by factors such as Environmental factors, including variability and range. School-age and productive-age groups with high mobility and people who are more often active outside the home have a greater risk of being exposed to malaria. Compared to those who spend more time indoors. Therefore, malaria prevention efforts are very important to avoid the spread of the disease